A longitudinal investigation of the role of perceived autonomy support from coaches in reducing athletes' experiential avoidance: The mediating role of subjective vitality. (January 2023) - Wang, Ying; Wu, Chia-Huei; Chen, Lung Hung
Abstract: Experiential avoidance, a personality trait that refers to individuals' tendency to avoid negative experiences, can have a negative impact on athletes' goal achievement. For this reason, it is crucial to identify the factors that can mitigate such a tendency. Drawing on self-determination theory and referring specifically to the function of subjective vitality, we first hypothesize that perceived autonomy support from coaches is positively associated with athletes' subjective vitality, which in turn is negatively associated with athletes' experiential avoidance. Data were collected from one hundred eighty-five high school athletes in Taiwan using a three-wave, time-lagged survey design spanning a period of seven months. These athletes were drawn from ten senior high schools and were in their second year of high school. The results of regression analysis showed that perceived autonomy support from coaches at Time 1 was associated with higher vitality among athletes at Time 2, which was, in turn, associated with lower levels of experiential avoidance at Time 3, conditional on the athletes' experiential avoidance at Time 2. While perceived autonomy support from coaches at Time 1 was also associated with lower experiential avoidance at Time 2, experiential avoidance at Time 2 was not associated with vitality at Time 3 after controlling for vitality at Time 2. The results of mediation analysis further supported the claim that vitality is a critical mediator of the relationship between perceived autonomy support from coaches and athletes' experiential avoidance. Implications concerning the identification of this mediator are discussed.